THE INFLUENCE OF NON-FINANCIAL COMPENSATION ON TURNOVER INTENTION OF GENERATION Z EMPLOYEES IN THE FOOD & BEVERAGES INDUSTRY WITH JOB SATISFACTION AS A MEDIATING VARIABLE - Suci Indah Syafitri; Rahdini Rizki Saragih; Naomi Karina Hutagalung; Siti Nurrahmawati Novitasari Hasyim; Ahmad Kodri Fauzi Hasibuan (RADJA PUBLIKA, 2026)
The high rate of employee turnover in the Food & Beverages industry has become a major challenge for companies in retaining human resources, particularly Generation Z employees who possess distinct work characteristics and expectations compared to previous generations. This study aims to analyze the effect of non-financial compensation on turnover intention among Generation Z employees in the Food & Beverages industry in East Medan District, with job satisfaction serving as a mediating variable. This research employed a quantitative approach using an accidental sampling technique. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with the assistance of SmartPLS 4 software. The results indicate that non-financial compensation has a negative and significant effect on turnover intention and a positive and significant effect on job satisfaction. Furthermore, job satisfaction has a negative and significant effect on turnover intention. The findings also reveal that job satisfaction mediates the relationship between non-financial compensation and turnover intention. These results suggest that providing adequate non-financial compensation, such as recognition, career development opportunities, supportive work environments, and positive workplace relationships, can enhance job satisfaction and reduce Generation Z employees' intention to leave the organization. The study contributes to the human resource management literature and provides practical implications for companies in developing effective employee retention strategies for Generation Z workers.